Integration of solar based charging station in power distribution network and charging scheduling of EVs - Shafiq, Aqib; Iqbal, Sheeraz; Rehman, Anis Ur; Elbarbary, Z. M. S.; Kotb, Hossam; Selim, Ali; Kamel, Salah (Frontiers in Energy Research, 2023)
The rapid development of electric vehicles (EVs) such as Easy Bike, Auto-Rickshaw, and Electric Bike is a major contributor to global energy concerns. Although electric vehicles are bringing a new dimension to the transportation sector, with advantages such as being the cheapest method of transportation and emitting fewer greenhouse gases (GHGs), the massive amounts of energy required to charge the electric vehicles is a challenging issue. Pakistan is also moving toward the use of electric vehicles however the absence of charging facilities in Pakistan slows down the charging process and increases the prices for electric vehicle users. Finding the requisite charging without threatening the current power infrastructure is one of the most challenging tasks of the present era. Renewable energy-based charging is required to fulfill the charging demand of electric vehicles. To find the best configuration to meet the necessary daily charging demand, this proposed work undertakes a techno-economic assessment for a novel renewables-based grid-tied charging station. The technical, economic and environmental impacts of Solar based grid-tied charging stations are taken into account. Moreover, the results are justified by considering the losses and building the system model. The suggested strategy decreases energy costs from .200/kWh to .016/kWh while reducing grid load by 254,030 kWh/yr. Furthermore, the system completes 7.7 charging sessions every day, using 13% of the electricity generated. The remaining 87% of the electricity is sold back to the grid, which generates significant revenue.